Non-invasive dual-brain stimulation facilitates social cooperation through enhancing interpersonal neural synchronization - Lifen Zheng; Chunming Lu (NeuroImage)
Reciprocal altruism-based cooperation is ubiquitous among humans and plays a crucial role in the survival and evolutionary trajectories of human beings. Prior research has been capable of comprehending social cooperation by examining the patterns of interpersonal neural synchronization (INS) during real bidirectional social interactions, rather than focusing on single-brain responses to external stimuli. However, the causal influence of INS on cooperative strategic behaviors remains unclear. To address this gap, we directly modulated the right temporoparietal junction (rTPJ)’s INS between individuals in 81 dyads during a Prisoner's Dilemma task using the transcranial direct current stimulation (tDCS) technique. The results indicated that active dual-brain tDCS on both individuals’ rTPJ during the task significantly enhanced INS, whereas sham dual-brain, control-region dual-brain, or single-brain stimulation had no such effect. This effect was further validated through an on-off mode of stimulation manipulation. Moreover, compared to sham dual-brain tDCS, the active dual-brain tDCS significantly increased the rate of cooperative strategic behaviors as well as the dyadic economic gains. Mediation analysis revealed that strategic behaviors mediated the relationship between INS enhancement and economic gains. These findings provide direct evidence for the crucial role of INS in social cooperation and offer a novel approach to promoting social cooperation.